ANALISIS PRODUKTIVITAS MELALUI PENGENDALIAN KUALITAS MATERIAL, KOMPONEN, DAN PRODUK JADI DENGAN PENDEKATAN SIX SIGMA PADA PROYEK LRT JABODEBEK DI PT INKA - -, Suseno; -, Cahyanto (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2020)
The Quality Assurance Division is the part responsible for the quality of Jabodebek's Light Rail Transit (LRT) products, or the railroad components in PT INKA. Defects in the under frame and water test were obtained as many as 70 units, in addition to the Production Planning and Control (PPC) section of the data resume of material & component adequacy, from the beginning of the project up to October 25, 2019, found a total of 29,395 NCR category findings ( No Conformity Report). This caused a decrease in the level of productivity of PT INKA. To increase company productivity, and to find out what internal factors are causing waste in the underframe test and water test on materials & components, as well as providing suggestions for improvement, the Six Sigma DMAIC method is used. The DMAIC cycle is a key process for continuous improvement towards the Six Sigma target. The steps taken are define, measure, analize, improve and control. DPMO value in the under frame and water test is 3,076.65 and has a sigma level of 4.524 and the material & component DPMO value is 2,587.92 and has a sigma level of 4.6060. The improvement phase is done is the company must focus on one of the projects, Perform tools maintenance, especially pneumatic bolt fasteners, do not use number two quality components or materials, the company should conduct further research or development and conduct training for employees.